Domestic Tourists' Perceptions of Sayan Tourism Village Product Components in Gianyar Regency - I Dewa Ayu Agung Diah Paramitha; Ni Putu Oka Agustini; Anom Hery Suasapha (Indonesian Journal of Applied and Industrial Sciences (ESA), 2025)
The purpose of this study was to understand the perception of domestic tourists towards the product components of Sayan Tourism Village in Gianyar Regency using six components of Tourism Village products, namely Attraction, Accessibilities, Amenities, Activity, Ancillary service and Available Packages. This research method uses a qualitative descriptive approach. With a sample of 100 domestic tourists who have visited Sayan Tourism Village. Sampling in this study will be taken randomly and is accidental. The data analyzed using a Likert scale. Data collection techniques using Questionnaire /survey, Observation, Documentation, and Literature Study techniques. The results of the study showed that overall, their perceptions of various aspects that influence the tourism experience were quite positive with the category "Good" for each variable. Sayan Tourism Village succeeded in providing a satisfying tourism experience, with the friendliness of the residents, natural beauty, and local culture as the main attractions. However, there are several aspects that need improvement, especially in spiritual tourism, supporting service organizations, toilet facilities, road conditions, challenging activities, and the availability of tour packages.